Consequents of functional and technical quality: evidence from electronic and mobile service industry in China. (2nd September 2014) - Dai, Hua; Midha, Vishal; Koong, Kai S.
The growing market potential of China's service industry requires an in–depth understanding of factors leading to consumers' loyalty towards e–service and mobile services providing websites. The growth of e–service and mobile services has changed the manner in which firms and consumers interact. A conceptual model that examines the relationship between service quality, trust, satisfaction, and loyalty in electronic and mobile environment is proposed. The analysis of data from 415 Chinese consumers reveals that both technical and functional quality of e–services and mobile services have a strong impact on consumers' trust and satisfaction, which in turn positively influence their loyalty towards service providers in electronic and mobile environment. We conclude our paper with a discussion of our findings and possible future research alternatives.